TERNAKLOKA : A WEB-BASED MARKETPLACE FOR QURBAN AND AQIQAH - Sri Wahyuni; Dini Julia Sari; Hernawaty Hernawaty; Nur Afifah (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: This research was conducted with the aim of overcoming the problems faced by conventional breeders, especially breeders in Kota Pari Village, namely obstacles in carrying out promotions outside the area, both outside the village and outside the province. In the conventional buying and selling process, the role of middlemen is also influential, resulting in low livestock prices for breeders and very expensive for buyers. The condition of the livestock has also decreased due to stress and their food is not maintained when they are marketed in traditional livestock markets. The transportation process also becomes expensive if the cattle do not sell well in the livestock market. The web-based application for qurbani animals and aqikah mar-ketpalce overcomes all the problems of conventional sales. Applications built using the PHP programming language and MySQL database. The website-based application for qurbani and aqikah animal marketplaces connects goat and cattle breeders in Kota Pari village with buyers who can be reached from various regions and all corners of the world. The application also provides various types of qurban and aqikah, both purchasing qurban and aqikah animals as usual or the choice of qurban and aqikah packages that have been cooked by the seller. So that the application built makes it easier for sellers and buyers of qurban animals and aqikah            Keywords: application; aqiqah; marketplaces; sacrifice                                                           Abstrak: Penelitian ini dilakukan dengan tujuan untuk mengatasi permasalahan yang dihadapi para peternak konvensional khusunya peternak di Desa Kota Pari, yaitu kendala dalam melakukan promosi diluar daerah baik luar Desa maupun luar provinsi. Pada proses jual beli konvensional peran serta tengkulak juga berpengaruh, sehingga mengakibatkan harga ternak menjadi murah untuk peternak dan menjadi sangat mahal untuk pembeli. Kondisi ternak juga menjadi menurun dikarekan setres dan makannya tidak terjaga pada saat dipasarkan di pasar ternak tradisional. Proses pengangkutan juga menjadi mahal jika ternak tidak laku dipasar ternak. Aplikasi Marketpalce hewan qurban dan aqikah berbasis website mengatasi semua permasalahan penjualan konvensional. Aplikasi yang dibangun menggunakan bahasa pemprogram PHP dan database MySQL. Apilkasi marketplace hewan qurban dan aqikah berbasis website menjadikan penghubung peternak kambing dan sapi di desa Kota Pari  dengan pembeli yang dapat dijangkau dari berbagai daerah dan seluruh penjuru dunia. Pada Aplikasi juga di sediakan berbagai jenis qurban dan aqikah, baik pembelian hewan qurban dan aqikah seperti biasa ataupun pilihan paket qurban dan aqikah yang sudha dimasak oleh penjual. Sehingga aplikasi yang dibangun memudahkan penjual dan pembeli hewan qurban dan aqikah. Kata kunci: aplikasi; aqikah; marketplace; qurban